2018
DOI: 10.1108/bfj-12-2017-0725
|View full text |Cite
|
Sign up to set email alerts
|

Eating habits of Polish university students depending on the direction of studies and gender

Abstract: Purpose The purpose of this paper is to evaluate the eating habits of students in the field of management and engineering of food products compared to students from faculties not related to food science. Furthermore, another aim is to conduct gender-wise assessment to determine the type of eating habit, i.e., careful or binge eating. Design/methodology/approach The research involved 400 students from all years of study. The survey was conducted in 2017–2018 and the selection of the sample was intentional. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
0
6
1
Order By: Relevance
“…A study conducted by [16] found that daily breakfast intake among Polish university students (42%) was lower than the 58% reported in the present study. On the number of meals, half (50%) of Polish students consumed 3-4 meals per day while the study results indicated that only 36% consumed 3 meals a day.…”
Section: Eating Habits Among University Studentscontrasting
confidence: 92%
“…A study conducted by [16] found that daily breakfast intake among Polish university students (42%) was lower than the 58% reported in the present study. On the number of meals, half (50%) of Polish students consumed 3-4 meals per day while the study results indicated that only 36% consumed 3 meals a day.…”
Section: Eating Habits Among University Studentscontrasting
confidence: 92%
“…Many students are for the first time in their life completely responsible for buying food and planning or preparing meals [ 5 , 6 , 37 , 38 ]. This is due to the decrease in involvement of children and youth in preparation of family meals, which results in the lack of cooking skills among young adults [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The estimated frequency of skipping meals in the young adult population ranges from 24 to 87% and is higher compared to other age groups [ 41 ]. Kowalska and Tarnowska [ 31 ] showed that women more often declared healthy eating. Most students ate 3–4 meals a day, and regular breakfasts were declared among 42 percent of respondents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Women were also found to have denser nutritional consumption and better adherence to recommended dietary guidelines compared to men (i.e., higher heathy eating index (HEI) component scores [ 29 ]). Additionally, there is strong evidence for sex differences in food choices based on motivation [ 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. In general, women tend to make food choices based on nutritional and health reasons while men are more likely to prioritize cost and taste [ 31 , 32 , 34 ].…”
Section: Introductionmentioning
confidence: 99%